GEOMETRICAL SCALE OF THE R CORONAE BOREALIS TYPE VARIABLES - Rosenbush, A. E. (Одеські астрономічні публікації, 2017)
The radii of R CrB and RY Sgr are obtained on published radial velosity measurings: 90 radii of the Sun: They are not differed from the Feast' data. The distance of permanent dust shell unconnected with visual minima is estimated: 100 radii of star. A dust connected with visual minima is formed at the distance of about 60 radii of star.